High-Quality Growth of GaInNAs for Application to Near-Infrared Laser Diodes. (11th November 2012) - Kondow, Masahiko; Ishikawa, Fumitaro
Abstract : GaInNAs was proposed and created in 1995. It can be grown pseudomorphically on a GaAs substrate and is a light-emitting material with a bandgap energy that corresponds to near infrared. By combining GaInNAs with GaAs, an ideal band lineup for laser-diode application is achieved. This paper presents the reproducible growth of high-quality GaInNAs by molecular beam epitaxy. Examining the effect of nitrogen introduction and its correlation with impurity incorporation, we find that Al is unintentionally incorporated into the epitaxial layer even though the Al cell shutter is closed, followed by the concomitant incorporation of O and C. A gas-phase-scattering model can explain this phenomenon, suggesting that a large amount of N2 gas causes the scattering of residual Al atoms with occasional collisions resulting in the atoms being directed toward the substrate. Hence, the reduction of the sublimated Al beam during the growth period can suppress the incorporation of unintentional impurities, resulting in a highly pure epitaxial layer.